Is The Dupont System Method Can Analyze Financial Reports? - Wahidullah, Wahidullah; Istiqomah, Istiqomah (Institut Agama Islam (IAI) SEBI, 2023)
The purpose of this research is to determine the calculation of financial report performance and the results of the analysis of Bank Mega Syariah's financial report performance for the 2012–2021 period using the DuPont System method. This research method uses a qualitative descriptive method. In the calculations and data analysis carried out on the performance of Bank Mega Syariah's financial reports for 2012–2021, it can be seen from 3 indicators, namely Net Profit Margin (NPM), Total Asset Turnover (TATO), and Return On Investment (ROI). From the results of the calculations carried out, we obtained fluctuating results with the average of the three indicators, namely Net Profit Margin of 37.7%, the average gain for the last ten-year period Total Asset Turnover was 0.22 times, and the average gain, the average Return On Investment score is 0.08%, which shows the performance assessment is based on the ROI criteria assessment, namely Unhealthy. Based on the results of the performance analysis based on the calculations obtained, namely the bank's ability to obtain net profits from low income, the company is not efficient in utilizing all its assets, and the company's ability to generate net profits is less efficient.